How is the career choice of a medical speciality dependent on gender inequality in the region - Lenka Šlegerová (Charles University in Prague, Institute of Economic Studies (IES), 2022)
Using a unique survey of almost 2,000 Czech and Slovak medical students run in 2020 and 2021, the paper investigates whether gender inequality and stereotypes as proxied by the gender unemployment rate gap drive students' choices of specialities. The data suggest that the higher the gender unemployment rate gap in the region (by 1 p.p.), the higher the probability its permanent residents choose a respective gender-dominated speciality (by 3.9 p.p.). This effect is driven by men in the sample. However, women report significantly more frequently encountering discrimination during the undergraduate training (41% vs 23%), presumably influencing their speciality choices. The study demonstrates the need to combat the prevalent gender stereotypes and discriminatory behaviour.
Keywords: I18; I23; J16; 330; gender inequality; medical speciality choice; unemployment gap